Degree of internationalization and performance: mediating role of innovation and moderating role of knowledge management system - Pouresmaeili, Hamideh; Ng, Siew Imm; Sambasivan, Murali; Raja Yusof, Raja Nerina (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
This study examines the relationship between degree of internationalization (DoI) and performance. Drawing on the inconclusive results in the DoI-performance relationship literature, this study draws attention to the mediating role of innovation. Despite a large body of literature on the relationship between innovation and performance, there is no consistent conclusion for this relationship. Hence, moderating role of knowledge management system (KMS) was empirically investigated in this study. The hypotheses were tested using 226 Malaysian internationalized firms. The results show a positive linear relationship between DoI and performance. Besides, the mediating role of innovation and the moderating role of KMS were empirically supported.